Peran Umpan Balim Bagi Mahasiswa Kedokteran - Herlina I.S Wungouw; Diana V. Doda (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: Feedback is an important part in teaching and learning process that serve as a catalyst to enhance learners’ achievement. In medical education, the importance of feedback has been recognized for learners at all level; undergraduate and postgraduate, in preclinical and clinical phases for more that twenty years. This literature review wants to explore what is the effective feedback for medical students and what are the factors that affect giving feedback?Method: Relevant literatures are selected as basis of recommendations on giving feedback in medical education.Results: The eighteen articles that fulfill the inclusion criteria have been collected from several resources include Medline, Pubmed and ERIC databases. Characteristics of effective feedback have been identified from those articles include positive, specific, private, well-timing, non-judgmental, interaction with sender, immediately given, from expert content, simple, and task oriented. While the factors affect giving feedback fall into four topics: the content of feedback, the method of delivery, sender credibility and training.Conclusion: Feedback in medical education has an essential role to enhance students’ learning behavior. Four factors that were affecting feedback delivery are content of the feedback, feedback delivery method, feedback provider’s credibility, and also training in feedback delivery.